An analysis of online purchase intention of Thai hostel accommodations - Wongkhajornpaibul, Kwanchart; Sornsaruht, Puris (My University, 2019)
Thailand's tourism sector has exploded in recent years, with expected international arrivals in 2019 projected at nearly 40 million, making it the 10th most popular destination on the planet. Furthermore, due to massive infrastructure expenditures, officials are further projecting 65 million visitors within the next ten years. Therefore, this study's purpose is to propose how these travelers' online purchase intention (PI) is affected by a hostel's website (HW), the accommodation booking website's personality (WP), the travellers' perceived value (PV), and the traveller's satisfaction (CS). From the sample group's 523 guests from 14 hostels, the LISREL 9.1 software program was used to analyze the confirmatory factor analysis (CFA), which was followed by a structural equation model (SEM) of the study's nine hypotheses. Results showed that all the model's causal factors had a positive influence on PI, with the variance of the factors influencing PI (R2) being 80%. Ranked in importance, factors affecting PI were WP, CS, PV, and HW, with total effect (TE) values of 0.64, 0.55, 0.54, and 0.29, respectively. The study is a literature study that is novel in that it further explores the esoteric idea of a 'website's personality,' and the subsequent use within a social media world. Furthermore, the sample group in Thailand can help other developing nations better understand how technologies can be blended to gain a better competitive advantage within the tourism sector.
Keywords: Customer satisfaction; Hostel website; Perceived value; SEM; Website personality